Medical management versus surgical management in fibroid uterus - Kurude, Vilas Namdev; Mutyapwar, Sneha Shekharreddy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Uterine fibroids (leiomyomas) are most common tumours of the uterine smooth muscles, appear to increase in incidence with age during reproductive years, with a peak in incidence between 35 to 40 years. Signs and symptoms of uterine fibroids include heavy or prolonged menstrual bleeding, pain and pregnancy complications. Current management strategies mainly involve surgical interventions, but choice of treatment is guided by patient’s age and desire to preserve fertility or avoid ‘radical’ surgery such as hysterectomy. Methods: It is the prospective observational study conducted in inpatients of department of OBGY at tertiary care hospital, admitted during the period of June 2019 to May 2021. Outcome measured in terms of relief of symptoms, decrease in size of fibroid, requiring subsequent surgery, quality of life, blood transfusion requirements, length of stay in hospital, successful pregnancies Results: Of patients treated with ulipristal, 78.57% had improved quality of life, in patients treated with leuprolide, 57.14% showed improved quality of life, with mifepristone 80% patients showed improved quality of life and with LNG 100% patients responded to it. All patients treated surgically, showed relief of symptoms. Conclusions: Medical line of management is best for patients in younger age group, small size fibroid, desire for future fertility. Uterus sparing option like myomectomy is done in patients not responding to medical line of management and desire for future fertility. Hysterectomy is definitive line of management for patients with fibroid uterus.